Comparison of Microbial Communities Isolated from Feces of Asymptomatic Salmonella-Shedding and Non-Salmonella Shedding Dairy Cows - Haley, Bradd J.; Pettengill, James; Gorham, Sasha; Ottesen, Andrea; Karns, Jeffrey S.; Van Kessel, Jo Ann S. (Frontiers in Microbiology, 2016)
In the United States Salmonella enterica subsp. enterica serotypes Kentucky and Cerro are frequently isolated from asymptomatic dairy cows. However, factors that contribute to colonization of the bovine gut by these two serotypes have not been identified. To investigate associations between Salmonella status and bacterial diversity, as well as the diversity of the microbial community in the dairy cow hindgut, the bacterial and archaeal communities of fecal samples from cows on a single dairy farm were determined by high-throughput sequencing of 16S rRNA gene amplicons. Fecal grab samples were collected from two Salmonella-positive cows and two Salmonella-negative cows on five sampling dates (n = 20 cows), and 16S rRNA gene amplicons from these samples were sequenced on the Illumina MiSeq platform. A high level of alpha (within) and beta diversity (between) samples demonstrated that microbial profiles of dairy cow hindguts are quite diverse. To determine whether Salmonella presence, sampling year, or sampling date explained a significant amount of the variation in microbial diversity, we performed constrained ordination analyses (distance based RDA) on the unifrac distance matrix produced with QIIME. Results indicated that there was not a significant difference in the microbial diversity associated with Salmonella presence (P > 0.05), but there were significant differences between sampling dates and years (Pseudo-F= 2.157 to 4.385, P < 0.05). Based on these data, it appears that commensal Salmonella infections with serotypes Cerro and Kentucky in dairy cows have little or no association with changes in the abundance of major bacterial groups in the hindgut. Rather, our results indicated that temporal dynamics and other undescribed parameters associated with them were the most influential drivers of the differences in microbial diversity and community structure in the dairy cow hindgut.